Plant Phyto-Chemicals as Plant-Producing Fungal Agents: A Review (International Journal of Innovative Research in Computer Science & Technology, 2022)
Plant fungus destroys vast swaths of  agriculture. Fungus has been connected to a number of  plant-based illnesses, posing considerable economic  challenges. Plant fungus seeks to get beyond the plant's  immune system by activating PAMP-triggered immunity  (PTI) and effector triggered immunity (ETI) defense.  Successful infections, on the other hand, may override  plant PTI and ETI, using pathogenic genes to defeat the  host plant's R-resistance genes, resulting in severe plant  diseases. Fungus spores tend to land on plant surfaces in  order to germinate, which requires perfect conditions such  as moisture, nutrients, and a suitable host. If the conditions  aren't right, it may still exist even if it's dormant. Chemical  fungicides have been used for many years, however there  have recently been indications that they are ineffective  against emerging fungal strains. Furthermore, chemical  fungicides are not biodegradable, posing a threat to the  environment. This review attempted to offer a concise  overview of plants that have anti-plant fungal properties.  Because plant extracts include a variety of possible anti fungal agents with various modes of action, the pesticide  industry may be able to produce plant-based fungicides on  a large scale.
Keywords: Fungicides; Fungal diseases; Plant fungi; Phytochemicals